POSSIBILITIES OF REDUCING COSTS IN ORDER TO INCREASE THE COMPANY'S FINANCIAL PERFORMANCE - BĂNUȚĂ MARIANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The analysis of the performance of any activity and especially of companies has always been a topic of great interest for a multitude of categories of information users. The article focuses on the financial performance of companies, on the relevant indicators for its analysis as well as on the presentation of ways to reduce costs that can contribute to increasing financial performance. Regarding the indicators which reflects financial performance, the result obtained (Income-Expenses) or the net accounting assets (equity) are the elements that enter into the calculation of most of them or that influence the factors that are taken into account in the calculation of the indicators. At the same time, the result obtained is an item of equity. Therefore, I can say that all these indicators are directly or indirectly influenced by the result obtained and consequently by the expenses/costs of the company. The centralization/decentralization of the company's activity, the monitoring of the indicators with which the performance is valuated, the delimitation of expenses into fixed and variable, the implications of applying the cost calculation methods, the relevance of costs are aspects covered in the article that can support the managers/owners of the company in the search for solutions to increase the financial performance of companies.